Hidden alpha - Ammann, Manuel; Cochardt, Alexander; Cohen, Lauren; Heller, Stephan (Journal of Financial Economics, 2026)
We provide novel evidence suggestive of insider trading through concealed relationships identified using information from over 100,000 Facebook profiles and their 35 million friends. Focusing on connections between fund managers and firm officers, we demonstrate that hidden ties are linked to substantial abnormal returns averaging 135 basis points per month (exceeding 16% alpha annually, t -stat = 3.54) across the universe of mutual funds and public firms. These hidden ties emerge as the most powerful predictor of future stock returns among documented network characteristics, with predictive power increasing over time through the present day. The premium associated with such connections arises not from endogenous selection or familiarity bias; instead, fund managers exhibit specific timing ability in deciding when to hold (or avoid) stocks of firm officers linked through hidden ties. The value of trading information rises with the degree of concealment and is concentrated around earnings and M&A events. The premium is absent in index funds, where strategic stock selection and timing are infeasible. Our findings on the value of hidden ties remain robust across industries, investment styles, time periods, and firm types.